Agrandamiento gingival inducido por medicamentos: fenitoína y ciclosporina a. Revisión bibliográfica - Flores Lozano, Grace Maribel (2022)
Gingival enlargement is a prevalent side effect in people undergoing treatment with medications such as phenytoin and cyclosporine A; the dental demand is generated when there is discomfort, pain, or when the aesthetic is compromised. Therefore, the present bibliographic review aims to know the influence of drugs such as phenytoin and cyclosporine A in gingival enlargement. To define the clinical characteristics of gingival enlargement induced by phenytoin and cyclosporine A, determine the mechanism of action of phenytoin and cyclosporine A on the gingival epithelium; to detail other predisposing factors that contribute to the formation of gingival hyperplasia induced by phenytoin and cyclosporine A. For the present research paper, a non- experimental, descriptive, analytical, and retrospective study was undertaken, which incorporated 22 scientific articles in English and Spanish, 4 theses, and 4 books obtained from the databases PubMcd, Google Scholar, McdLinc, Cochranc Library Plus. From the analysis undertaken, the most common clinical characteristics in gingival enlargement due to drugs such as phenytoin and cyclosporine A are inflammation in papillae areas with reddish coloration circumscribed for gingival margins in 100% and chewing, esthetic problems in 100%. We also observed that 100% of the articles reviewed mentioned that the most common predisposing factor was bacterial plaqueand 81% inflammation. Regarding the mechanism of action of phenytoin, 100% of the articles reviewed describe that it stimulates the proliferation of fibroblast populations; on the other hand, 81% of the scientific manuscripts described that the mechanism of action for Cyclosporin A modifies signaling in fibroblasts and increases the secretion of interleukin 6